Diseño del plan estratégico de gestión de la junta parroquial de Tumbabiro, cantón Urcuquí, provincia de Imbabura, para mejorar la calidad de vida de sus habitantes durante el quinquenio 2010 al 2015 - Posso Salgado, Gustavo Xavier (2011)
The application of strategic planning will allow self-sustaining, tourism projects, generate employment positions, avoid migration target resources and incentives for the education of their young children undertake large projects and programs covering community services and avoid uncertainty and discontent of the population in the future because the matrices have plans for five years and significantly decrease the pressure on the junta, and provide quality management.